LABORATORY EVALUATION OF CIKERUH RIVER AGGREGATE AS A MATERIAL OF ASPHALT CONCRETE BINDER COURSE MIXTURE - SUHERDIAN (NIM 26900007), AVIP
The deposit of aggregate material along Cikeruh river in the Majalengka is huge and it is the source of road making material for Cirebon area. This research evaluated the engineering properties of Cikeruh aggregate and the use of the aggregate for asphalt concrete course. Tests were conducted to investigate the properties of the aggregate, and evaluated the performance of bituminous mixture. The results of engineering properties were as follow; Los Angeles abrasion of Cikeruh aggregate was 21,03% and Banjaran aggregate was 15,14%. Aggregate impact for Cikeruh aggregate was 11,34% whereas Banjaran aggregate was 10,28. Aggregate crushing for Cikeruh aggregate was 19,99% whereas Banjaran aggregate was 15,10%. Ten percent fines for Cikeruh aggregate was 18 tones, whereas Banjaran aggregate was 25 tones. Flakines Cikeruh aggregate was 22,88% whereas Banjaran aggregate was 19,96%. Elongation of Cikeruh aggregate is 20,62% whereas Banjaran aggregate is 18,74%. Soundness for Cikeruh aggregate is 2,24% whereas Banjaran aggregate is 0,17% and affinity for bitumen Cikeruh aggregate and Banjaran aggregate were about 95%, All two mixes had similar structure and particle as indicated by chemistry and mineralogy tests, and microscopic electron scanning. Marshall method was used in the mix design and Marshall test were conducted. The optimum binder content obtained were 5,95% for AC with Cikeruh aggregate and 6,15% for AC with Banjaran aggregate. The Marshall stability, flow, MO, VIM, VMA, VFB resulted from the Marshall test for AC with Cikeruh aggregate were 1097 kg, 3,61 mm, 303,7 kg/mm, 4,24%, 15,3%, 72,2% respectively and that for AC with Banjaran aggregate were 1135 kg, 3,72 um, 305,2 kg/rm, 4,87%, 16,2%, 69,9% respectively. The index of retained stability of the AC with Cikeruh aggregate was 92,18% and that with Banjaran aggregate was 93,00%, the indirect tensile strength of the AC with Cikeruh aggregate was 49,9 psi and that with Banjaran aggregate was 56,1 psi. The Resilient Modulus of the AC with Cikeruh aggregate was 2102 Mpa, and that with Banjaran aggregate was 2124 Mpa. The permanent deformation of the AC with Cikeruh aggregate was 1,69 mm that with Banjaran aggregate was 1,60 mm. 93,00%. The condussion was the tests results indicated that the Cikeruh aggregate engineering properties were a little bit lower than Banjaran aggregate, but it satisfied and full filled the engineering properties requirement for the asphalt concrete course.